Phytochemical constituents and pharmacological activities of Picrasma javanica: quassinoids interest - Bakhtiar, Muhammad Taher; Mohd Razali, Najah Fatehah; Darnis, Deny Susanti; Rahman, Md. Atiar; Artasasta, Muh Ade; Zakaria, Zainul Amiruddin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Picrasma javanica Blume is a plant belonging to Simaroubaceae. It is known for its secondary metabolites, namely quassinoids, offering various pharmacological properties including antitumor, antimalarial, and antiviral. The plant is traditionally used as a source medicine for different diseases in Myanmar, Thailand, and Indonesia. Despite the extensive studies on P. javanica, there is no concise and conclusive information regarding the phytochemical and phytochemistry of the plant has been reported. Thus, we aimed to discern the phytochemical constituents and pharmacological activities of P. javanica. The phytochemical constituents and pharmacological benefits of P. javanica were reviewed and supported from previous in vivo and in vitro studies. The literature used in this review were retrieved from electronic database such as Scopus, Semanticscholar, Sciendirect, Google scholar, Researchgate, Pubmed, and websites. P. javanica possesses several phytochemical constituents, such as quassinoids, alkaloids, and triterpenoids. The compounds of the plant have been isolated and studied for their pharmacological activities, encompassing antimalarial, antiproliferative, antiviral, antimicrobial, and membrane-stabilizing activities. It was found that the pharmacological activities in the plant were attributable to the key ingredients of quassinoids and alkaloids present. However, further extensive studies must be carried out to explore more potential benefits that the plant could offer.